2021
DOI: 10.1186/s13102-021-00363-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported experience of orofacial injury, preventive practice, and knowledge of Iranian adolescent martial art athletes towards sports-related orofacial injuries

Abstract: Background Increased engagement of adolescents in martial arts exposes them to a relatively high risk of experiencing orofacial injuries. We evaluated self-reported experience of orofacial injuries, preventive practice, and knowledge of management of sport-related orofacial injuries and related factors in adolescent Karate and Taekwondo athletes in Iran. Methods This cross-sectional study was conducted on Iranian martial arts athletes including Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 35 publications
(65 reference statements)
0
13
1
6
Order By: Relevance
“… 8 , 21 , 29 However, the present study's findings are comparable to that of studies conducted in middle eastern countries such as Iran and Saudi Arabia. 24 , 30 Although avulsion was the least experienced injury, it is well known that it has the worst prognosis, and its early management plays a crucial role in treatment success. 10 Therefore, training efforts should be directed toward coaches to increase their awareness of the importance of early intervention and appropriate management of avulsed teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 21 , 29 However, the present study's findings are comparable to that of studies conducted in middle eastern countries such as Iran and Saudi Arabia. 24 , 30 Although avulsion was the least experienced injury, it is well known that it has the worst prognosis, and its early management plays a crucial role in treatment success. 10 Therefore, training efforts should be directed toward coaches to increase their awareness of the importance of early intervention and appropriate management of avulsed teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have reported that a single lecture was not enough to train people on managing dental trauma emergencies. 30 , 31 Although this explanation remains an assumption that needs further study; it sheds light on the urgent need to develop educational and training programs to provide coaches and other groups with the knowledge and skills to avoid negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…A falta de conhecimento e a crença na ineficácia dos protetores bucais são razões para a falta de capacidade dos atletas em usar estes dispositivos 2,3,12 . Na literatura, alguns estudos incentivam educadores e profissionais de saúde a informar os esportistas sobre as formas disponíveis de prevenção de lesões 2,3,10,16 .…”
Section: Discussionunclassified
“…Crianças e adolescentes (C/A) são frequentemente afetados por lesões dentárias traumáticas (LDTs) e, no período de dentição mista, há uma alta incidência destas lesões [1][2][3] . As atividades esportivas são um importante fator etiológico das LDTs nos dentes permanentes anteriores.…”
Section: Introductionunclassified
See 1 more Smart Citation